2015
DOI: 10.1021/es504437s
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Carbon Quality and Sorption of Organic Pollutants in the Baltic Sea in Light of Future Climate Change

Abstract: Regional climate change scenarios predict increased temperature and precipitation in the northern Baltic Sea, leading to a greater runoff of fresh water and terrestrial dissolved organic carbon (DOC) within the second part of the 21st century. As a result, the current north to south gradient in temperature and salinity is likely to be shifted further toward the south. To examine if such climate change effects would cause alterations in the environmental fate of organic pollutants, spatial variations of DOC qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Furthermore, 10 larval perch individuals were added to each mesocosm as top consumer. Two variables were altered in a 2 × 2 factorial design: DOC concentration and pollutant addition; and identical mesocosm treatments were exposed to two temperatures (15 and 18°C), as described in detail by Ripszam et al (2015b) . However, temperature treatment was excluded from the study to focus on the role of pollutants and tDOM, both parameters considered to be major climate change-related issues in this region ( Andersson et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 10 larval perch individuals were added to each mesocosm as top consumer. Two variables were altered in a 2 × 2 factorial design: DOC concentration and pollutant addition; and identical mesocosm treatments were exposed to two temperatures (15 and 18°C), as described in detail by Ripszam et al (2015b) . However, temperature treatment was excluded from the study to focus on the role of pollutants and tDOM, both parameters considered to be major climate change-related issues in this region ( Andersson et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pollutants can have various effects on marine ecosystems, such as direct toxicity, persistent negative effects, or bioaccumulation ( Kallenborn et al, 2012 ; Andersson et al, 2015 ). Furthermore, the physicochemical environment can alter the behavior of these substances ( Ripszam et al, 2015a , b ). Moreover, the northern hemisphere is predicted to undergo an increased precipitation regime, leading in turn to higher terrestrial runoff and increased river inflow (up to 15–22%) to the Baltic Sea by the end of the century ( Meier et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a spiking experiment, we demonstrated that the sorption of structurally diverse pollutants to dissolved organic matter in seawater varies between areas of the Baltic Sea (Fig. 2 ) (Ripszam et al 2015 ). The distribution constant between water and DOC (log K DOC ) for hexachlorobenzene and phenanthrene, representing halogenated aromatic and polycyclic aromatic compounds, respectively, decreased from north to south in the Baltic Sea, while tributyl phosphate, representing compounds with polar functional groups and relatively high water solubility, showed no geographical variation.…”
Section: Effects Of Increased Doc Inflow On Organic Pollutant Sorptiomentioning
confidence: 93%
“…Hurricane Irene alone which occurred in 2011 is estimated to have contributed to 19% of the 2011 annual dissolved organic matter (DOM) exports from a forested catchment in Cecil County, Maryland (Dhillon and Inamdar, 2013). Areas of mean temperatures of about 5 C and 30 C would have 10% and 3% carbon loss respectively with a temperature increase of 1 C. The change in temperature would also influence the bioavailability and toxicity of pollutants since adsorption processes are temperature dependent (Ripszam et al, 2015). The activity of microbial organism is further enhanced as humic substances act as electron donors acceptors during anaerobic respiration (Lau et al, 2015;Lipczynska-Kochany, 2018b).…”
Section: Introductionmentioning
confidence: 99%